Teacher knowledge and views of the response to intervention initiative - Gallagher, Alissa (My University, 2010)
Since Congress added new provisions to federal educational laws (IDIEA, 2004; NCLB, 2001), a progressive movement in education called Response to Intervention (RTI) has become more widely known. Embedded in the framework of RTI is the expectation that classroom teachers will become proficient at such things as: using data to inform instruction, monitoring student progress, and adopting research-based teaching strategies. The purpose of the current study was to conduct a preliminary investigation of how educators would self-report their knowledge, views, and skills related to seven core principles and components of the RTI initiative. Current study findings found that special education teachers and school support staff reported significantly more knowledge and more positive views of RTI then did general education teachers. Primary teachers also reported more knowledge and feeling more supported in their efforts to implement RTI than did secondary teachers. Specific groups of teachers that need to be targeted for future professional development in RTI related areas, along with educational settings that would benefit from professional development and school-wide reorganization were identified, and implications of these findings were discussed.
Keywords: Learning disabled children -- Identification; Response to intervention (Learning disabled children) -- Evaluation